If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -2(z + 1) = 3z + -1(20 + -5z) Reorder the terms: z + -2(1 + z) = 3z + -1(20 + -5z) z + (1 * -2 + z * -2) = 3z + -1(20 + -5z) z + (-2 + -2z) = 3z + -1(20 + -5z) Reorder the terms: -2 + z + -2z = 3z + -1(20 + -5z) Combine like terms: z + -2z = -1z -2 + -1z = 3z + -1(20 + -5z) -2 + -1z = 3z + (20 * -1 + -5z * -1) -2 + -1z = 3z + (-20 + 5z) Reorder the terms: -2 + -1z = -20 + 3z + 5z Combine like terms: 3z + 5z = 8z -2 + -1z = -20 + 8z Solving -2 + -1z = -20 + 8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8z' to each side of the equation. -2 + -1z + -8z = -20 + 8z + -8z Combine like terms: -1z + -8z = -9z -2 + -9z = -20 + 8z + -8z Combine like terms: 8z + -8z = 0 -2 + -9z = -20 + 0 -2 + -9z = -20 Add '2' to each side of the equation. -2 + 2 + -9z = -20 + 2 Combine like terms: -2 + 2 = 0 0 + -9z = -20 + 2 -9z = -20 + 2 Combine like terms: -20 + 2 = -18 -9z = -18 Divide each side by '-9'. z = 2 Simplifying z = 2
| 3x+6=6-x | | p^2-12p+45=0 | | x^2+2x^2-900=0 | | 4/25•2/5= | | 4(2x+5)=-17+5 | | 1 = c2 | | q+7=9 | | 7r=60-5R | | 3 = d2 | | 7-4(4-(3y-7))=0 | | F(4)=x+9 | | 16y^3/20y^4 | | -45=-3x+18 | | 5a^2-a-20=0 | | -7/2x=-28 | | 3w^2-7w=6 | | (x-1+3i)(x-1-3i)=0 | | -3(5x+6)=-84 | | 1:1000/1:100×250 | | -4(-5x+6)=84 | | 2t=t+15 | | -6(3x-8)=102 | | 6-3x=9x | | -15-3x=-6x+27 | | 1/c=0.15 | | 6x-10=14+2x | | (s-4)(2s+2)(s^2-2)= | | 5x-34=74-4x | | 162x-82=738 | | 4(3n+3)=7(6n+7)+1 | | -162x-82=738 | | x-36=-4x+39 |